Rheumatic Valvulopathy in Sub-Saharan Africa: A Cross-Sectional Study of Cameroonian Urban Schools - Chris Nadège Nganou-Gnindjio; Anicet Gakdang Ladibe; Joël Marie Obama Nyaga; Sandrine Laure Ngambono; Loic Alban Tasong; Jules Thierry Elong; Hursul Geffried Nzongang; Félicité Kamdem; David Chelo (Global Heart)
Background: Rheumatic heart disease is a post-infectious sequelae of acute rheumatic fever resulting from an abnormal immune response to streptococcal pharyngitis that triggers valvular damage. It is the most commonly acquired heart disease in children, particularly in developing countries. Objective: This study aimed to describe rheumatic valvulopathy among schoolchildren and adolescents in Yaoundé, Cameroon. Methods: A cross-sectional echocardiography study was conducted from December 2022 to May 2023 among students aged 5 to 19 in primary and secondary schools in Yaoundé, Cameroon. All students with informed parental consent and who agreed to participate in the study were included. The data collected were entered and analysed using SPSS statistics software version 23.0. The association between the qualitative variables was verified using Odd-Ratio with a 95% confidence interval and a significance level of 5%. Results: Of the 1020 children recruited, 133 (13.03%) had rheumatic heart disease with a mean age of 11.69 ± 4.09 years. The sex ratio (M/F) was 0.56. Most of the participants lived in urban slums (60.9%). Cardiac murmurs were detected in 23 (17.3%) participants during auscultation, with the majority (78.3%) being located at the mitral focus. The definitive form of rheumatic heart disease was observed in 69 (51.9%) children. Mitral involvement was observed in all participants. Mitral valve abnormalities were primarily characterized by mitral insufficiency in 124 (93.2%) participants, valvular thickening (74.4%), and restriction of movement (42.9%). Age between 10 and 14 years [OR = 2.36; CI = (1.11–5.01)] and residence in urban slums [OR = 2.14; CI = (1.05–4.36)] were significantly associated with an increase in the occurrence of definitive rheumatic valve disease. Conclusion: Rheumatic heart disease is common among schoolchildren in this setting. It systematically affects the mitral valve. The clinical presentation is usually silent at first.